High sensitivity CW-cavity ring down spectroscopy of water in the region of the 1.5 μm atmospheric window; Journal of Molecular Spectroscopy; Vol. 227, № 1 - Maco P.; Romanini D.; Mikhailenko S. N. Semen Nikolaevich; Naumenko O. V.; Kassi S.; Jenouvrier A.; Tyuterev Vl. G.; Campargue A. (2004, 2004)
Title screen